2011
DOI: 10.1079/dmpp/20113166052
|View full text |Cite
|
Sign up to set email alerts
|

Tuta absoluta . [Distribution map].

Abstract: A new distribution map is provided for Tuta absoluta Meyrick. Lepidoptera: Gelechiidae. Hosts: tomato (Solanum lycopersicum), potato (S. tuberosum), black nghtshade (S. nigrum), jimsonweed (Datura stramonium) and tree tobacco (Nicotiana glauca). Information is given on the geographical distribution in Europe (Albania, Bulgaria, Cyprus, France, Corsica, Mainland France, Germany, Greece, Crete, Mainland Greece, Hungary, Italy, Mainland Italy, Sardinia, Sicily, Lithuania, Malta, Netherlands, Portugal, Mainland Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the Mediterranean area, native parasitoids and predators can play an important role in attacking Tuta absoluta eggs. [23][24][25][26] 26 This seems to be the case of Macrolophus pygmaeus Rambur (Hemiptera: Miridae) [27][28][29][30] and Trichogramma achaeae (Hymenoptera: Trichogrammatidae). [31][32][33] Laboratory and field studies using Trichogramma achaeae against Tuta absoluta have shown promising results in glasshouses tomatoes of the Azores, 33 but an effective control of pest populations was not achieved due to a low rate of parasitism.…”
Section: Introductionmentioning
confidence: 99%
“…In the Mediterranean area, native parasitoids and predators can play an important role in attacking Tuta absoluta eggs. [23][24][25][26] 26 This seems to be the case of Macrolophus pygmaeus Rambur (Hemiptera: Miridae) [27][28][29][30] and Trichogramma achaeae (Hymenoptera: Trichogrammatidae). [31][32][33] Laboratory and field studies using Trichogramma achaeae against Tuta absoluta have shown promising results in glasshouses tomatoes of the Azores, 33 but an effective control of pest populations was not achieved due to a low rate of parasitism.…”
Section: Introductionmentioning
confidence: 99%
“…While not included in the study of van Lenteren et al, 21 it later appears 9 as a valuable natural enemy of lepidopterans pests, commercialized in Europe for the first time in 2012, and having a market value rated of 'medium' due to 10,000 to a 100,000 individuals sold per week. The shift of the commercial importance of Trichogramma achaeae and the increasing number of scientific studies using M. pygmaeus as model pest species 25,33,64,65 may have been a consequence of the invasion of Europe by Tuta absoluta, a major pest of tomato crops. 10 The current major concerns with Tuta absoluta together with the increase of scientific research, makes its natural enemies valuables market products for the near future.…”
Section: Benefit-cost Analysis (Investor/factory Perspective)mentioning
confidence: 99%
“…Consequently, there is a growing need for a paradigm shift from insecticides to more efficient, safer and eco-friendly pest management options. Biological control, particularly entomopathogenic fungi (EPF), has emerged as a promising alternative to insecticides for managing insect pests (Keçeci and Öztop, 2017;Vega and Kaya, 2012;CABI, 2021). Moreover, entomopathogenic species have virulence factors to cause disease and kill insect pests (Vega and Kaya, 2012).…”
mentioning
confidence: 99%
“…Moreover, entomopathogenic species have virulence factors to cause disease and kill insect pests (Vega and Kaya, 2012). Entomopathogenic fungi (EPF) are one of the types of biological control agents to combat P. absoluta (CABI, 2021). Using naturally existing indigenous or exotic entomopathogen fungi species such as Metarhizium anisopliae and Beauveria bassiana are effective bioagents and have been recommended and reported as they are pathogenic to tomato leaf miners (Youssef, 2015;Shiberu and Getu, 2017).…”
mentioning
confidence: 99%